The influence of articulatory suppression on the control of implicit sequence knowledge - Gaillard, Vinciane; Destrebecqz, Arnaud; Cleeremans, Axel (Frontiers in Human Neuroscience, 2012)
The present study investigated the consciousness-control relationship by suppressing the possibility to exert executive control on incidentally acquired knowledge. Participants performed a serial reaction time (SRT) task, followed by a sequence generation task under inclusion and exclusion instructions and a sequence recognition task. The generation task requires control on the sequential knowledge that has been incidentally acquired. We manipulated the possibility for participants to recruit control processes in the generation task in three different conditions. In addition to a control condition, participants generated sequences under inclusion and exclusion concurrently with either articulatory suppression or foot tapping. Results suggest that articulatory suppression specifically impairs exclusion performance by interfering with inner speech. Because participants were nevertheless able to successfully recognize fragments of the training sequence in a final recognition task, this is suggestive of a dissociation between control and recognition memory.